Development of Oral Health Model for Primary Caregivers of 6-12-month-old Children in Kongrha - Disatan, Kasamonrat; Pithpornchaiyakul, Samerchit; Youravong, Nattaporn (Area Based Development Research Journal, 2022)
The oral health survey in 2019 indicated that the amount of caries incidence of 18-month-old children in Kongrha district, Phatthalung province was higher than that in the provincial, county, and national levels. As a result, this study was designed to develop and evaluate new oral health education for primary caregivers of 6–to 12-month-old children by dental nurses and village volunteers in Kongrha district, Phatthalung province. The first phase involved planning and developing a new oral health education scheme through a workshop and group discussion about oral health education for children’s caregivers. The second phase deals with providing new oral health education to 81 primary caregivers of children by dental nurses and village volunteers. The primary caregivers are trained on the newly-proposed oral health education that includes discussion among primary caregivers, practicing tooth brushing skills, and consultation given by village volunteers during monthly home visits. The third phase focuses on the interviews with the primary caregivers about the acquired knowledge, self-efficacy, and behavior regarding tooth brushing for their children. Interviews were conducted six months before and after the study. The study results were analyzed using McNemar statistics with a 95 percent confidence level. The findings significantly indicated that the primary caregivers had gained more knowledge and more confidence in brushing the children’s teeth, as well as provided better practice in oral health care for children. Therefore, this newly-proposed oral health education is most likely practical and beneficial for sustainable development.